O domorodnosti alpskega kozoroga v Sloveniji - Neve Repe, Andreja (Gozdarski vestnik, 2023)
Alpine ibex (Capra ibex) is an Alpine endemic species. In the area of Slovenia, the species is supposed to have been eradicated in the second half of the 17th century, and globally, it was on the brink of extinction due to the overhunting at the end of the 19th century. Only the population in the wider area of the Gran Paradiso Park on the utmost west part of the Alps in Italy. Due to the reintroductions and other protection programs, alpine ibex now inhabits the entire Alps, including Slovenia. However, its populations in Slovenia are declining and are in a very poor condition, which can be a result of several factors. Inbreeding resulting from small founder populations, historical bottlenecks, and colony isolation has compromised genetic diversity, potentially impacting demographic outcomes as well. In addition, diseases could have added to the decline of the species. Immediate conservation measures are necessary for the long-term conservation of alpine ibex in Slovenia, with a prerequisite being the proper determination of the species’ nativeness, as it was previously misclassified as non-native due to insufficient data. In our article, based on the archeozoological, genetic, and preliminary habitat analyses we explain that the alpine ibex is an autochthonous species in Slovenia. In our studies, we have shown that the species lived in the area of the present Slovenia in the late antiquity and early medieval era. We also preliminarily determined suitability and connectivity of the alpine ibex habitat in the Slovenian Alpine region and indicated the probable measures needed for the conservation of the species in Slovenia.
Keywords: Alpe; Alpes; Capra ibex; genetics; genetika; habitat; izvornost vrste; programi varstva; protection programs; species nativeness